In Vivo Cell and Tissue Dynamics Underlying Zebrafish Fin Fold Regeneration - Mateus, Rita (Public Library of Science, 2012)
BACKGROUND: Zebrafish (Danio rerio) has a remarkable capacity to regenerate many organs and tissues. During larval stages the fin fold allows the possibility of performing long time-lapse imaging making this system very appealing to study the relationships between tissue movements, cell migration and proliferation necessary for the regeneration process. RESULTS: Through the combined use of transgenic fluorescently-labeled animals and confocal microscopy imaging, we characterized in vivo the complete fin fold regeneration process. We show, for the first time, that there is an increase in the global rate of epidermal growth as a response to tissue loss. Also enhanced significantly is cell proliferation, which upon amputation happens in a broad area concerning the amputation level and not in a blastema-restricted way. This reveals a striking difference with regard to the adult fin regeneration system. Finally, an accumulation of migratory, shape-changing fibroblasts occurs proximally to the wound area, resembling a blastemal-like structure, which may act as a signaling center for the regeneration process to proceed. CONCLUSIONS: These findings provide a novel in vivo description of fundamental mechanisms occurring during the fin fold regeneration process, thereby contributing to a better knowledge of this regenerative system and to reveal variations in the epimorphic regeneration field.